HUKUM HAJATAN SAMPAI MENUTUP JALAN UMUM - Lailatul Mubarokah; Sudirman Sudirman (Raudhah - Proud To Be Professional, 2023)
Islam is here to provide peace and tranquility for mankind. This was brought and taught by the Messenger of Allah in Islam. Islam teaches humans to obey the laws in it which are sourced from the Al-Qur'an and Sunnah. Included in the legal study of closing roads due to walimah, Islam provides guidance by weighing and looking at the disadvantages and advantages. This study uses a qualitative approach using a type of literature study. The data collection technique used in this research is documentation with several sources such as books, web articles, and journals. The results of this study are in Islamic law regarding road closures because walimah should not be carried out because it remembers the basic law which refers to the verses of the Koran which state that it includes acts of tyranny and hurting others. However, there are scholars who allow road closures because of walimah with several conditions including guaranteeing the safety of others, obtaining permission from the government, and providing alternative roads